2023
DOI: 10.3389/fonc.2023.1103320
|View full text |Cite
|
Sign up to set email alerts
|

Combining neoadjuvant chemotherapy with PD-1/PD-L1 inhibitors for locally advanced, resectable gastric or gastroesophageal junction adenocarcinoma: A systematic review and meta-analysis

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) have shown promising prospects in locally advanced, resectable gastric or gastroesophageal junction adenocarcinoma (GC/GEJC) immunotherapy, but their efficacy in neoadjuvant settings remains unclear. This study aimed to assess the efficacy and safety of integrating programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) inhibitors into neoadjuvant chemotherapy (NACT) of GC/GEJC treatment.MethodsPubMed, Cochrane Library, Embase, ClinicalTrials.gov, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Our study revealed that 13 (21.3%) and 27 (44.2%) older patients with GC in the NICT-MIG group achieved pCR and MPR, respectively. These findings indicate a comparable tumor response in older patients, aligning with previous studies conducted across all age populations [ 22 ]. We also found the comparable 2-year OS and RFS between two groups, especially for pTNM satege I patients undergoing upfront MIG and ypTNM stage 0-I patients who had better tumor response in the NICT-MIG group.…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed that 13 (21.3%) and 27 (44.2%) older patients with GC in the NICT-MIG group achieved pCR and MPR, respectively. These findings indicate a comparable tumor response in older patients, aligning with previous studies conducted across all age populations [ 22 ]. We also found the comparable 2-year OS and RFS between two groups, especially for pTNM satege I patients undergoing upfront MIG and ypTNM stage 0-I patients who had better tumor response in the NICT-MIG group.…”
Section: Discussionsupporting
confidence: 91%
“…The limitations in the efficacy of current immunotherapies, mainly involving immune checkpoint inhibitors, have emphasized the need to enhance our comprehension of combination therapeutic strategies for improving outcomes among patients who exhibit poor response to single-agent immunotherapy ( 27 ). To further enhance the efficacy of neoadjuvant therapy in patients with advanced gastric adenocarcinoma, multimodal treatment regimens incorporating neoadjuvant chemotherapy and PD-1 antibody immunotherapy prior to surgical resection are being increasingly employed ( 28 ). However, the choice of population for neoadjuvant chemotherapy in combination with PD-1 antibody therapy remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment process of many tumors, including gastric and ovarian cancer, general perspectives indicated that the combination of chemotherapy and immunotherapy can synergistically improve the effect of anti-cancer. This might be due to the reduced immune suppression of TME with the combination of chemotherapeutics and the enhanced elimination and recognition of tumors by the immune system 10,11 . PD-L1 blockade in combination with chemotherapy has already been applied in combination with chemotherapy in several clinical trials.…”
Section: Introductionmentioning
confidence: 99%